Instagram For Dummies, 2nd Edition - Herman, Jenn (Indianapolis John Wiley and Sons, 2022)
Are you on Insta? Start sharing pictures and a lot, lot more Instagram For Dummies helps you navigate Instagram and all the updates coming to the platform. For new and experienced users, this book keeps you in the know, so you can post to your feed, create Reels and Stories, broadcast and watch live video, and so much more. This handy guide covers creating Reels to attract more followers, adding updates and stickers for stories, and the addition of multiple feeds so you can customize your experience. There are so many new features coming to this ever-more-popular social platform, you need a friend like Dummies to help you keep up. Create viral content, or just share cat pics with your close friends and family. Learn the basics of the Instagram app and web interfaces Get started with your first posts, Stories, and Reels Discover the many new features that are making Instagram more fun than ever Find out how to make your posts scroll-stopping and more popularThis is the perfect how-to guide for both newbie and experienced social media users who need a guide on setting up Instagram, expanding their audience, and doing more on the app.
Includes index (243-255).
Keywords: Online social networks